Abortion and the early church Christian, Jewish and pagan attitudes in the Greco-Roman world - Gorman, Michael J. 1955- (Downers Grove, IL IVP, 1982)
Includes bibliographical references and index.
Keywords: Abortion -- religious aspects -- Cristianity -- history; Civilisation, Greco-Roman.; Abortion -- religious aspects -- Judaism -- history; Civilisation, pagan